2016
DOI: 10.1051/matecconf/20167400032
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Fatigue of Die-Casting Dies: An Overview

Abstract: Abstract.Coupled studies by experimental and numerical simulations are necessary for an increased understanding of the material behaviour as related to the interaction between the thermal and mechanical conditions. This paper focus on the mechanisms of thermal fatigue in the failure of dies and cores used in the die casting of aluminum alloys. The thermal fatigue resistance is expressed by two crack parameters which are the average maximum crack and the average cracked area. Samples of various types of H13 ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Knowledge about microstructural evolution of such kind of steels, as well as the result of thermal history, is fundamental to achieve the expected mechanical behavior and corrosion resistance. The time-temperature history, derived from industrial heat treatments or welding processes [141][142][143], may lead to precipitation of various compounds (e.g., chromium carbides and nitrides) and some other intermetallic phases (e.g., σ phase). The formation of such compounds leads to losses in both corrosion resistance and fracture toughness [144].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Knowledge about microstructural evolution of such kind of steels, as well as the result of thermal history, is fundamental to achieve the expected mechanical behavior and corrosion resistance. The time-temperature history, derived from industrial heat treatments or welding processes [141][142][143], may lead to precipitation of various compounds (e.g., chromium carbides and nitrides) and some other intermetallic phases (e.g., σ phase). The formation of such compounds leads to losses in both corrosion resistance and fracture toughness [144].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The thermal fatigue damage is a function of thermal gradient and thermal expansion coefficient of the material. According to Abdulhadi et al [18], compression stresses developed exceed the elastic limit of the die material only if the integration of the temperature gradient and the widespread thermal expansion is high enough. In the present case, when the coolant channel position is increased from 0.5 to 1 mm, there is no considerable change in temperature distribution (figure 5b) and hence thermal gradient does not contribute for increase in fatigue damage.…”
Section: Effect Of Coolant Channel Position On Fatigue Damagementioning
confidence: 99%
“…Carbon nanotubes have been expected as the perfect material to increase the properties of solid materials owing to their strength, high elastic modulus, and aspect ratio. Several types of research have shown that incorporating CNTs into metals, ceramics, and polymers can dramatically enhance their mechanical properties [9][10][11][12][13]. Multi-walled carbon nanotubes are one of the best materials that can be used as reinforcement materials due to its excellent properties [10,14].…”
Section: Introductionmentioning
confidence: 99%